KOMPARASI TEORI KEBENARAN MO TZU DAN PANCASILA: RELEVANSI BAGI PENGEMBANGAN ILMU PENGETAHUAN DI INDONESIA - Budisutrisna, Budisutrisna (Jurnal Filsafat "WISDOM", 2016)
Mo Tzu's theory of truth and the truth of the theory of Pancasila both using three understand the truth, namely: coherence, correspondence, and paragmatik. However, both theories are necessary dikomparasikan truth. Necessary to find similarities and differences. Then look for relevance to the development of science in Indonesia as a country based on Pancasila. This study is a literature. The method used in this research is a philosophical hermeneutic method, with the following elements: description, historical continuity, comparison and reflection. The results showed that there are some similarities and differences between the theory of truth Mo Tzu and Pancasila. Relevance to the development of science in Indonesia, that the truth must be coherent with the values of Pancasila, should correspond to the reality of God, man, one, people, and fair. In addition, the truth must be beneficial for humanity which believes God, keeps unitary, democratic, and justice.